The effect of vibrational devices on pain in patients undergoing orthodontic treatment: A systematic review and meta-analysis - Shilpa Chawla; Lishoy Rodrigues; Shailesh Deshmukh; Gaury Anant Vajarekar (Wolters Kluwer Medknow Publications, 2022)
Objective: To critically evaluate the existing evidence with respect to the effect of vibrational devices on pain levels during orthodontic treatment. Materials and Methods: Unrestricted electronic search in PubMed/MEDLINE, Directory of open access journal, Cochrane Central as well as manual searches was conducted up to June 2020. Only randomized-controlled trials (RCTs) were included. Study selection, data extraction, and bias assessment were done by two independent reviewers. The Cochrane risk-of-bias tool was used, and the quality of evidence was graded using the grading of recommendations assessment, development, and evaluation approach. A fixed-effects meta-analysis of continuous data, with its 95% confidence intervals (CIs), was used. Results: Nine RCTs were included for qualitative synthesis and the overall quality was moderate and had an overall low risk of bias. Several shortcomings were observed because of the lack of blinding of the participants as well as the investigators. We conducted a meta-analysis for two studies which assessed the pain using (visual analog scale) which showed (standard mean difference 1.83, 95% CI, −7.18-10.84) with fixed effect model based on the heterogeneity value of I2. Results also showed a statistically nonsignificant difference regarding the effect of vibrational devices on pain levels when compared with no vibratory stimulus and sham devices. Conclusions: There is weak evidence indicating the effect and use of vibrational devices in orthodontic treatment. The meta-analysis aided us to conclude that there is no significant difference in the pain outcome after the use of vibrational devices as compared to the control group and having no effect on pain levels in patients undergoing orthodontic treatment.